MAKNA SIMBOLIK TOKOH WAYANG SEMAR DALAM KEPEMIMPINAN JAWA - Nurcahyo, Jati (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
This paper intends to reveal some teaching of the Javanese Leadership found in some Javanese literaturesas well as wejangan (advice). These teaching generally exposed variety of moralethics. The leadership philosophy also exhibits a natural form of creativity, sense, initiative and work in addition. These teaching require a leader to have attributes of â€œKsatria Utamaâ€ This is Ksatria who is expected to apply the concept of â€œJumbuhing Kawula Gustiâ€. This concept becomes the foundation power, leadership and humanity. In this way, he is believed to be able to realize his country as one which is prosperous and peaceful.A letter who is capable to be a â€œPrior Knightâ€ is a person who has morality and characteristic as symbolized in the character of the puppet â€œSEMARâ€ in Javanese culture. â€œSemarâ€ as a servant is able to defent â€œRaja Dewaâ€ (The King of God) and â€œBathara Guruâ€. This capability is created when the mind reflects higher thinking level or wise opinion, then this mind will guide the leader Semar in this his wise character is capable to normalize the general prosperity. Keywords :Puppet, Semar,Leadership